Observation of standard breaststroke technique stability - Silva, A.; Freitas, J. R. J.; Conceicao, A.; Campaniço, J.; Matos, T.; Leitão, L.; Louro, H. (Biomechanics and Medicine in Swimming XI - Abstracts, 2010)
INTRODUCTION: The aim of this study was to create an instrument to collect data for analysis of the technical stability in swimming. This instrument will serve as a base for the observed behavior during the cyclic execution in the breaststroke technique. In this context, using qualitative analysis through the observational methodology, the study focused on the characterization of the motor patterns of behavior in the breaststroke technique on elite athletes. METHODS: The instrument consisted of a system of field formats, based on references of observational methodology and biomechanical models of swimming, giving special emphasis to six taxonomic criteria that aggregate in the form of alpha-numeric codes the crucial information to describe behaviors that define the breaststroke technique. The quality of the instrument was analyzed using the kappa Cohen the software-GSEQ SDIS (Bakeman & Quera, 1996), based on the records of seven trained observers, and, for accuracy effects, another expert. RESULTS: The kappa Cohen results ranged between 0.94 and 0.98, guaranteeing the accuracy and objectivity when describing technical approaches with this instrument. The behavioral stability changes accordingly to the swimmer and also between the stages and observed moments, however each swimmer fits the technical model. DISCUSSION: We can consider that, given the high values of agreement between the expert and the seven observers, the instrument is appropriate to observe the conduct of technical Breaststroke swimmers in context situations.